Can a Monitoring Agency efficiently regulate the EU milk market? - Sascha A. Weber; Heiko Hansen (Johann Heinrich von Thünen-Institut, 2014)
[Synopsis] In light of the expiry of the EU milk quota in April 2015, the German Federal Association of Dairy Farmers (Bundesverband Deutscher Milchviehhalter e. V. (BDM)) and the European Milk Board (EMB) have put forward a proposal for the future management of the dairy market. The central element of this proposal is a Monitoring Agency which will not only monitor the milk market on a permanent basis and analyse developments but also implement a Market Responsibility Programme in the event of a crisis. Both the number and amount of market adjustments should be carried out in a flexible manner, depending on the market situation. Based on the calculated milk production costs, a target price range is defined in which the average European milk producer price should move. This system requires the introduction of both a basic volume and supply rights. Depending on the market situation, supply rights amounting to 3-5 percent of the existing (basic) supply rights will be granted to or withdrawn from dairy farmers. As an additional intervention measure, a remunerated scheme for the voluntary suspension of production in the tendering or bidding process should be implemented, together with strategic storage. The costs of the instruments are to be covered from a market regulation fund Furthermore, in order for this system to function, the existing regulation on protection at the EU's external borders on the basis of the Uruguay Round must be maintained (Fink-Keßler A 2013). [...]
urn:nbn:de:gbv:253-201412-dn054618-3
Keywords: 630